Dynamic Pricing as an Innovative Tool for the Marketing Pricing Policy of an Enterprise - LUNOVA, T. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article examines the essence of dynamic pricing as an innovative tool for the marketing pricing policy of an enterprise. It is substantiated that dynamic pricing contributes to flexibility, adaptability and increased efficiency of the enterprise’s activities in the modern market. The advantages and risks of its application in the digital economy are analyzed. Among the advantages of this method, the following are highlighted: increased profitability and competitiveness of the enterprise, flexibility in responding to market changes, optimization of inventory management, and the possibility of personalizing price offers. The risks of dynamic pricing include the following: negative perception by consumers, increased requirements for information technology, the possibility of pricing errors, the risk of price wars, as well as legal and ethical restrictions. The experience of leading world companies that successfully use dynamic pricing is studied, including Amazon, Uber, Booking.com, Walmart, Zara. The algorithm for setting prices for Bolt and Uklon taxi rides on the Ukrainian market is characterized, and factors that influence the dynamic part of the tariff are identified. The possibilities and limitations of implementing dynamic pricing at Ukrainian enterprises have been assessed. It is noted that the use of this method at Ukrainian enterprises remains limited due to the insufficient level of business digitalization, lack of analytical tools and risks of consumers’ perception of frequent price changes. Practical recommendations for the application of this pricing method in Ukrainian companies are proposed.